Annealing of InGaAlAs digital alloy studied with scanning-tunneling microscopy and filled-states topography - Offermans, P; Koenraad, PM; Wolter, JH; Song, JD; Kim, JM; Bae, SJ; Lee, YT (AMER INST PHYSICS, 2003)
We have investigated the structural properties of as-grown and annealed (750 and 800 degreesC) digital alloy InGaAlAs (lambda=1.3 mum) laser structures by cross-sectional scanning-tunneling microscopy. We show that it is possible to resolve the digital alloy period in the as-grown sample and the 750 degreesC annealed sample. The 800 degreesC annealed sample did not show the digital alloy period because of intermixing of the digital alloy. The 750 degreesC annealed sample showed only slight intermixing. The barrier/well interface roughness for the as-grown and the 750 degreesC annealed samples was the same. Annealing at 800 degreesC showed large barrier/well interface roughness and lateral composition modulation due to the phase separation of InGaAs/InAlAs alloys. (C) 2003 American Institute of Physics.